Rising incidence of systemic autoimmune inflammatory rheumatic diseases during the COVID-19 pandemic: a geographical cohort study - Marina Davoli; Silvia Laura Bosello; Enrico De Lorenzis; Salvatore Soldati; Mirko Di Martino; Maria Antonietta D’Agostino; Gerlando Natalello; Paolo Parente; Andrea Barbara (RMD Open)
Objective The natural infection with SARS-CoV-2, or vaccination against it, has been postulated to directly contribute to an increase in the incidence of autoimmune inflammatory rheumatic diseases (AIIRDs). Conversely, preventive measures limiting access to healthcare services could have resulted in missed or delayed AIIRD diagnoses or have reduced the infection rate of any triggering infections. We aimed to define real-life trends in AIIRD diagnoses from the prepandemic period through 2023 in a large and geographically circumscribed population of 6.5 million inhabitants.Methods AIIRDs’ annual diagnosis rates from 2017 to 2023 were derived from the registration of disease-specific exemption codes of the resident population of Lazio, a highly populated region in central Italy. Incidence rate ratios (IRRs) were calculated to compare pandemic and average prepandemic rates (2017–2019). Poisson regression was used to define statistically significant changes.Results A total of 16 254 AIIRD diagnoses were registered over the 7-year period. The average prepandemic incidence of AIIRDs was 4.81 per 10 000 inhabitants (95% CI 4.69 to 4.92). Compared with the prepandemic period, the diagnosis rate decreased in 2020 (IRR 0.68, 95% CI 0.64 to 0.72) but remained above prepandemic levels in 2021, 2022 and 2023. In 2023, there was a 22% increase in AIIRD incidence compared with prepandemic levels (IRR 1.22, 95% CI 1.17 to 1.28, p<0.001). This excess incidence was primarily driven by increases in both primary arthritides and systemic rheumatic diseases.Conclusions We observed a temporary decline in diagnosis in 2020, followed by a substantial increase from 2021 to 2023. This trend (decline and increase) may be linked to COVID-19 infection or to the reduction and subsequently potential increase of other infectious triggers following the use of preventive measures, such as facial masks and social distancing.